Alexis de Tocqueville y la tradición liberal (2008)
The article tries to find inside Tocqueville ́s thought his contributions tothe liberal tradition, understanding that this tradition has been growingfrom time to time, thanks to the contribution of different persons, eachone has contributed to give shape and to consolidate what now we calland know as “liberalism”